A study of consumer behavior and willingness to pay towards cosmetic products of generation Z in Hochiminh city - Bich Tran Hien Thi; Duy Nguyen Phuong Ngoc; Vo Trung Quang; Nguyen Viet Nhu; Dieu Nguyen Thao Ho; Kristina Susi Ari; Endarti Dwi (BIO Web of Conferences, 2023)
The global cosmetics industry is experiencing robust growth and Generation Z (Gen Z) is a potential customer source of this market. This research examines customers’ intentions to purchase cosmetic goods of Gen Z in Hochiminh city using perceived value factors as the antecedents of attitude in the model. A cross-sectional study, applying a convenient sampling method, was conducted to collect data from Gen Z people in January 2023. There were no specific cosmetics products included in the study. Descriptive analysis and Partial Least Square (PLS) method of Structural Equation Modeling (SEM) with SmartPLS 4.0.8.7 software were used to analyze the research data. The PLS-SEM analysis of 723 responses showed that attitudes toward purchasing cosmetic products are significantly positively impacted by perceived environmental value. A more positive attitude would result from increased brand credibility and product understanding of cosmetics. There was no evidence to support the impact of other perceived values (specifically, health, safety, social, spiritual, and ethical) on attitudes toward consumer behavior. Attitude was important in predicting willingness to pay (both direct and indirect). This study helps industry professionals to advance the qualities of cosmetic products by increasing and improving environmental value, product knowledge, and brand credibility. The eco-friendly pattern of production and marketing strategies focusing on product ingredients, manufacturing processes, and quality standards are necessary to enhance brand credibility and product understanding, align with consumer preferences and achieve greater success in the market.